Assessing quality care in kidney disease: The double‐edged sword versus the Gordian knot. Issue 1 (8th January 2020) - Weiner, Daniel E.
Abstract: Assessing quality is essential for optimizing clinical care but remains challenging. Too many measures can result in dilution of quality improvement efforts, distracting providers from delivering the most meaningful care, whereas too few measures can devalue important domains of care. Similarly, performance standards that are too high can result in unintended consequences, including diminishment of patient input into their individualized care and cherry picking. Valid quality metrics assess measureable aspects of care that are both clinically meaningful and modifiable, and, in the absence of quality metrics and performance standards, optimal care is at risk. Quality measures are an indelible part of the health care system, composing a pillar of value‐based purchasing, and balancing these aspects of quality assessment is essential for patient care. This review summarizes the quality systems in nephrology, focuses on current dialysis quality metrics and the strengths and limitations of current measures, and emphasizes the value of a parsimonious set of meaningful metrics with performance standards that both incentivize optimal practices while allowing sufficient latitude to individualize care for kidney patients.